2019
DOI: 10.1007/s10433-019-00512-2
|View full text |Cite
|
Sign up to set email alerts
|

Card playing enhances speech perception among aging adults: comparison with aging musicians

Abstract: Speech perception and auditory processing have been shown to be enhanced among aging musicians as compared to nonmusicians. In the present study, the aim was to test whether these functions are also enhanced among those who are engaged in a non-musical mentally challenging leisure activity (card playing). Three groups of 23 aging adults, aged 60-80 years, were recruited for the study: Musicians, Card players, and Controls. Participants were matched for age, gender, Wechsler Adult Intelligence Scale-III Matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
9
1
Order By: Relevance
“…This finding is consistent with a study showing no benefit of a 6‐month piano training in older adults (Fleming et al, 2019). However, it is in contrast to previous aging studies showing that playing a musical instrument as amateurs (Fostick, 2019; Zendel & Alain, 2012) or professionals (Bidelman & Alain, 2015; Parbery‐Clark et al, 2011) have small but positive effects on SPiN. It is also at odds with longitudinal studies that have shown that attending a short amateur training, such as a 6‐month piano‐based training (Zendel et al, 2019) or a 10 weeks of choral singing (Dubinsky et al, 2019), positively affect SPiN.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…This finding is consistent with a study showing no benefit of a 6‐month piano training in older adults (Fleming et al, 2019). However, it is in contrast to previous aging studies showing that playing a musical instrument as amateurs (Fostick, 2019; Zendel & Alain, 2012) or professionals (Bidelman & Alain, 2015; Parbery‐Clark et al, 2011) have small but positive effects on SPiN. It is also at odds with longitudinal studies that have shown that attending a short amateur training, such as a 6‐month piano‐based training (Zendel et al, 2019) or a 10 weeks of choral singing (Dubinsky et al, 2019), positively affect SPiN.…”
Section: Discussioncontrasting
confidence: 76%
“…Here we used a syllable discrimination task and we found no global singing effect on SPiN. The studies showing a behavioral effect of musical activities on SPiN used sentences or word repetition tasks (Dubinsky et al, 2019; Fostick, 2019; Parbery‐Clark et al, 2011; Zendel et al, 2019; Zendel & Alain, 2012), with the exception of Bidelman and Alain (2015), which used a vowel‐continuum categorization task. The other previous study that did not find musical advantage used a sentences‐picture‐naming task (Fleming et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Additionally, Ruggles et al, [ 22 ] observed a significant correlation in speech-in-noise abilities with years of music training in adults. In older adults, musicians additionally out-perform non-musicians in sentence-in-noise [ 23 , 24 ] and word-in-noise discrimination [ 23 , 25 ]. Fostick, 2019 demonstrated that the musician advantage for words-in-noise discrimination remained when comparing older adult musicians to life-long card players.…”
Section: Introductionmentioning
confidence: 99%